Relationship between Stress Levels and Sleep Quality of Breast Cancer Patients Undergoing Chemotherapy at Dharmais Cancer Hospital, DKI Jakarta Province in 2022 - Umi Salamah; Yuni Susilowati; Ayu Pratiwi; Bernardo Oliber A. Arde (Universitas Nahdlatul Ulama Surabaya, 2023)
Breast cancer ranks first for women worldwide, with an incidence rate of 40 per 100,000 women with a death rate of 21.5% per year. It is estimated that around 15% of all female deaths worldwide are caused by breast cancer. Breast cancer causes physical and psychological problems simultaneously related to the disease or its treatment. One of the most common disturbances in breast cancer patients is stress. Stressors that breast cancer patients constantly face can impact the disruption of the hormone melatonin and increase adrenaline and cortisol hormones, resulting in disturbed sleep quality of cancer patients. Research objective: To determine the relationship between stress levels and sleep quality in breast cancer patients undergoing chemotherapy. Research method: Correlational quantitative research with a cross-sectional approach. The total sample is 156 breast cancer patients taken by purposive sampling technique. Results: The results of the univariate analysis showed that most breast cancer patients undergoing chemotherapy at Dharmais Cancer Hospital experienced severe stress (51.9%), and most had poor sleep quality (60.9%). The results of the bivariate analysis showed that there was a significant relationship between stress levels and sleep quality in breast cancer patients undergoing chemotherapy at the Dharmais Cancer Hospital in 2022 (p-value: 0.000). Conclusions and Suggestions: It is hoped that the hospital will carry out stress management in cancer patients by providing health education or with relaxation techniques. So, it is hoped that this can improve the sleep quality of cancer patients